Designing Effective National Programs to Improve Industrial Energy Efficiency - Liu, Feng; Tromop, Robert (World Bank, Washington, DC, 2016)
This guidance note, about Industrial energy efficiency is closely linked to the economic competitiveness of countries with significant manufacturing bases and to the energy security of countries that rely heavily on imported energy. For individual enterprises, improving energy efficiency strengthens the bottom line, often reducing direct energy costs by 10 to 30 percent Industry accounts for approximately 30 percent of global final energy consumption and a similar share of carbon dioxide (CO2) emissions. Its total energy intensity could be reduced by about 25 percent by modernizing technology, particularly in developing countries. The main barriers to achieving broad energy efficiency gains are insufficient information; difficulty obtaining financing; and, in many developing countries, insufficient capacity for identifying, preparing, and delivering projects. A welldesigned national industrial energy efficiency program should include clear policy goals linked to tangible targets; a range of policy instruments to guide and encourage action; and measures to build implementation capacity and facilitate financing. The role of the government is to facilitate or even to mandate the removal of impediments to successful investment in energy efficiency. Carefully calibrated interventions can address local and global environmental concerns while generating social and economic benefits. Governments should take a leadership role by analyzing how energy drives productivity and how improvements in energy efficiency can increase the bottom line. Further information about this note can be seen here in : http://www.iipnetwork.org/IEE.